Formulating a New Pharmaceutical Drug; Acetaminophen Tablet Containing N-acetyl Cysteine, To Alleviate the Severity of Liver Damage in Rats: Phase I, Animal Study - Mehrpour, Omid; Dastjerdi, Mohammad; Nakhaee, Samaneh; Amirabadizadeh, Alireza; Bijari, Bita; Roumi, Hesam; Hosseini, Mehran (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Acetaminophen (APAP) is a commonly used analgesic and also the leading cause of medication-induced liver damage. On the other hand, N-acetylcysteine (NAC) is a medication widely used to treat APAP overdose. Despite this interest, a few studies have investigated the co-administration effects of these medications. Therefore, this study aimed to evaluate the effects of NAC and APAP on renal and liver functions in rats when they use concurrently. Methods: Male Wistar rats were orally treated with a single dose of APAP (700 mg/kg) alone or in combination of NAC at the three different doses (200, 500, and 700 mg/kg). After 24 hours, the blood and liver samples were collected for biochemical and histopathological evaluations. Results: Liver damage was well established in the 700 mg/kg APAP-treated rats, as evidenced by elevated the plasma levels of aspartate transaminase (AST) and alanine transaminase (ALT). In addition, the plasma level of blood urea nitrogen (BUN) was significantly increased in the APPA group compared to the control group. Moreover, histological examinations revealed that liver degeneration was evident in APAP-treated animals. NAC only at the highest dose (700 mg/kg) could inhibit ALT elevation, but had no effect on AST and BUN levels. Interestingly, co-administration of NAC (700 mg/kg) with APAP (700 mg/kg) could slightly shift liver histological alterations from the irreversible stage (fibrosis) toward reversible lesions such as necrosis and hemorrhage. Conclusion: The study findings indicate that co-administration of NAC and APAP can reduce the severity of APAP-induced liver damage in rats. *Corresponding Author: Mehran Hosseini; Email: mehranhosseiny@bums.ac.ir; ORCID: https://orcid.org/0000-0002-6793-2035 Please cite this article as: Mehrpour O, Dastjerdi M, Nakhaee S, Amirabadizadeh A, Bijari B, Roomi H, Hosseini M. Formulating a New Pharmaceutical Drug; Acetaminophen Tablet Containing N-acetyl Cysteine, To Alleviate the Severity of Liver Damage in Rats: Phase I, Animal Study. Arch Med Lab Sci. 2021;7:1-8 (e14). https://doi.org/10.22037/amls.v7.35528